UJI AKTIVITAS ANTIOKSIDAN PADA EKSTRAK ETANOL 70% TANAMAN TERATAI PUTIH (Nymphaea nouchali L) - Yulianita Pratiwi Indah Lestari; Raudatul Patimah; Mustika Muthaharah; Rizka Mulya Miranti; Tuty Mulyani; Aris Purwanto (Bajang Institute, 2023)
Many aquatic plants grow in these rivers, one of which is the lotus. Lotus (Nymphaea) is a plant that often lives in the swamplands of South Kalimantan, especially Banjarmasin. The lotus is a wild plant in its natural habitat, which is not foreign to Indonesian people. Some Indonesian people only know about the beauty of this plant. It turns out that apart from its beauty, the lotus also has benefits for curing various diseases. The lotus plant can also be used as medicine because it contains several different chemical ingredients in each part. This research aims to determine the antioxidant activity of extracts from various parts of the White Lotus plant (Nymphaea nouchali L) using the DPPH method. The plant parts tested include: flower parts, flower stalks, leaves and petioles. Based on the research results, the highest antioxidant activity test was found in flower extract, namely with an IC50 value of 66.906 μg/mL, and the lowest was found in leaf extract, namely with an IC50 value of 99.449 μg/mL. Quercetin as a comparison standard has an IC50 value of 6.337 μg/mL with a